A Note on Multiplicative Uncertainty and Partisan Policies - Massimiliano Castellani; Antonello E. Scorcu (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2004)
In this paper we consider the effects of «multiplicative» uncertainty about the structure of the economy in the standard partisan model. An increase in the uncertainty decreases of the inflation rate pursued by the liberal policymaker, but increases the inflation rate pursued by the conservative policymaker. For certain configurations of the parameters, an increase in the uncertainty reduces the expected loss of both parties.
Keywords: 330; Ökonomische Theorie der Demokratie; Inflation; Theorie